Event-specific earnings management: additional evidence from US M&A pre-and post-SOX. Issue 1 (10th April 2017) - Alsharairi, Malek; Dixon, Robert; Al-Hamadeen, Radhi
Abstract : Purpose: The purpose of this paper is to re-examine the motivation to manage earnings in US mergers and acquisitions (M&As) by investigating whether the enactment of Sarbanes-Oxley act (SOX) has affected pre-merger earnings management. Design/methodology/approach: The authors used a sample of over 700 completed M&As of US public firms during 1999-2008. Using quarterly reports, they tracked down earnings management during the four quarters preceding the deal and consequently drew inferences about the implications of SOX on interim reporting practices. Findings: We report evidence that in the post-SOX era, non-cash acquirers begin pre-merger upwards earnings management in an earlier quarter than in the pre-SOX era. Further, our evidence indicates that in the quarters prior to the takeover, targets engage in more aggressive upwards earnings management in the post-SOX era. Originality/value: Unlike what is anticipated regarding earnings management practices after SOX, the study reveals significant evidence of upward earnings management by firms engaging in M&A in post-SOX era.